2021
DOI: 10.1111/liv.14973
|View full text |Cite
|
Sign up to set email alerts
|

Impact of major depression and antidepressant use on alcoholic and non‐alcoholic fatty liver disease: A population‐based study

Abstract: Background and Aims The effect of major depression and antidepressant use on patient survival in chronic liver disease is unknown. We evaluated the impact of major depressive disorder (MDD) and antidepressants on survival among patients with alcoholic liver disease (ALD) and non‐alcoholic fatty liver disease (NAFLD). Methods The Health Improvement Network database, the largest medical database in the United Kingdom, was used to identify incident ALD (n = 4148) and NAFLD (n = 19 053) in patients between 1986 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…Bile acids participate in a range of important host functions such as monoamine neurotransmitters, short-chain fatty acids, and indoles [ 75 ]. Non-alcoholic fatty liver disease has complex pathogenic mechanisms for MDD [ 76 ]. In addition, the liver is involved in the metabolism of many stress hormones, and neurotransmitters, for example, Cytochrome P450 (CYP), which is primarily expressed in the liver, are some of the main metabolizers of glucocorticoids and monoamines in the peripheral system [ 77 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…Bile acids participate in a range of important host functions such as monoamine neurotransmitters, short-chain fatty acids, and indoles [ 75 ]. Non-alcoholic fatty liver disease has complex pathogenic mechanisms for MDD [ 76 ]. In addition, the liver is involved in the metabolism of many stress hormones, and neurotransmitters, for example, Cytochrome P450 (CYP), which is primarily expressed in the liver, are some of the main metabolizers of glucocorticoids and monoamines in the peripheral system [ 77 ].…”
Section: Monoamine In the Digestive Systemmentioning
confidence: 99%
“…A recent study using the electronic medical records database from the United Kingdom showed higher survival rates among patients with the diagnosis of NAFLD and major depressive disorder compared to those without major depressive disorder 18 . However, the findings in the referenced study did present a caveat that major depressive disorder and antidepressants in patients with NAFLD were not independent predictors of improved decompensated cirrhosis‐free survival over a median 3‐year follow‐up 18 . These findings in this study can be explained by linkage‐to‐care and closer follow‐up with healthcare providers as a consequence of comorbid major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These findings in this study can be explained by linkage‐to‐care and closer follow‐up with healthcare providers as a consequence of comorbid major depressive disorder. In addition, this study utilized Read code (such as ICD‐10 code) to define NAFLD, which may underestimate the accurate prevalence and incidence of NAFLD, as reflected by only 19,053 cases of NAFLD over 20 years 18 . The association between depression and NAFLD is well established, 13 as well as an association between advanced fibrosis in metabolic dysfunction‐associated fatty liver disease and depression 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of substantial observational studies support the concept that MDD may increase the risks of GID (Fang et al, 2019; Kim et al, 2019; Martín-Merino, Ruigómez, García Rodríguez, Wallander, & Johansson, 2010). Despite the plausible positive association between MDD and GID, there is also partial evidence to support the claim is non-existent (Kim et al, 2013; Lee, Otgonsuren, Younoszai, Mir, & Younossi, 2013; Shaheen, Kaplan, Sharkey, Lethebe, & Swain, 2021). Observational studies yield inconsistent results, and the real direction of causal association cannot be ascertained owing to measurement error, confounding, and reverse causality bias (Fewell, Davey Smith, & Sterne, 2007).…”
Section: Introductionmentioning
confidence: 99%